Identify Human Error In Using Mobile Device That Lead To Security Threat - Abdul Mubin, Norzul Masri (2017)
Human errors are the most critical issues that contributes to the information security threat. Mobile device are the main devices that can be manipulates by the attacker towards their victims. The attackers nowadays more interested in attacking the mobile devices because of the current trend which the users used their mobile devices to perform all their daily task and stores their data inside the mobile devices. Users always think that it would be easier to stores all the information inside their mobile devices but did not concern the risk of their actions. This research are used to identify the human errors in using mobile device that contributes to the information security threat. The first part of this reports will identify and discuss in details of the common human errors from the previous research result and also the possible attack related to the errors perform. The second part will explain about the research process in details such as the method that will be used to perform the research, the research objective, research scope and goals and many more. The questionnaires are the method used to collect all the data from the user to identify the most common human error in using mobile devices. The guidelines from other researcher are also identify in this research to ensure that the new guideline proposed are the best practice guidelines that can be used by all users. The comparison between the literature review, questionnaires and the previous guidelines are the used to design the new guidelines. The research will be proposed a best practice security guidelines that applicable for the mobile device user to reduce and minimize the risk of become the victims of the cybercrime.